Cold agglutinin-mediated autoimmune haemolytic anaemia associated with diffuse large B cell lymphoma. (10th July 2018) - Wongsaengsak, Sariya; Czader, Magdalena; Suvannasankha, Attaya
Abstract : Cold agglutinin-mediated autoimmune haemolytic anaemia is associated with the development of autoantibodies that can agglutinate red blood cells at cold temperatures. While primary cold agglutinin disease is an idiopathic lymphoproliferative disorder, secondary cold agglutinin syndrome (CAS) complicates other diseases such as infections, autoimmune diseases and cancers, mostly low-grade lymphomas. Early recognition, treatment of CAS and treatment of its associated underlying diseases are crucial to a successful outcome. We report a case of CAS in a setting of diffuse large B cell lymphoma, in which the treatment course was complicated by worsened anaemia due to chemotherapy-induced myelosuppression. We reviewed previously reported cases and discussed diagnosis and treatment strategies, including novel complement inhibitors, as potential future therapy.